Climate change's effects on women: Iraq as an example - Zghir, Ansam Ali (Journal of Humanities & Social Sciences, 2023)
Natural events such as earthquakes and hurricanes, as well as man-made activities such as fast urbanization, population increase, agricultural intensification, and other factors, cause the Earth's climate to change.Women, on the other hand, have more risks and responsibilities than males because they are more likely to be economically reliant and have less access to knowledge and information that would enable them to manage climate-related hazards to agricultural and animals.Women are more vulnerable to climate-related disasters and extreme weather events than males, owing to regional cultural norms and unequal distribution of responsibilities, resources, and power, particularly in underdeveloped nations like Iraq.Even in times of drought and lack of food and water supplies, their contribution to preventing climate change is rarely recognized, despite the fact that they prioritize their families.We examine climate change and its impact on women in several climate change scenarios in this research. Agriculture, biodiversity, water, natural catastrophes, conflicts, migration, pollution, health and sanitation, education, security, social, psychological, and human rights are all examples of these issues. Various ideas are also explored with some international finance agencies in attempt to reduce these consequences.We aim through this research to enhance knowledge of the effects of climate change, especially on women, in order to sensitize those concerned to think about finding appropriate solutions, since climate change has become a reality and fast.The research dealt with the descriptive method, in addition to the analytical method in reading and discussing the data.According to the research, the biggest threat to our species' survival is climate change, and women are more susceptible to it than men because of their reliance on natural resources, daily responsibilities, and financial level. In light of this, the researcher made a list of recommendations for the national Iraqian government, organizations, and civil society activists to help Iraqi women reduce the effects of the climate catastrophe.
Keywords: climate change; impact of climate change; Iraq's climate; women